Imagery ability of elite level athletes from individual vs. team and contact vs. no-contact sports - Di Corrado, D.; Guarnera, M.; Vitali, F.; Quartiroli, A.; Coco, M. (PeerJ, 2019)
Background: In the sport context, imagery has been described as the condition in which persons imagine themselves while executing skills to deal with the upcoming task or enhance performance. Systematic reviews have shown that mental imagery improves performance in motor tasks Methods: The aim of the present study was to explore whether imagery vividness (i.e., the clarity or realism of the imagery experience) and controllability (i.e., the ease and accuracy with which an image can be manipulated mentally) differ by sport types (team vs. individual and contact vs. non-contact). Participants were athletes from team contact and non-contact sports (rugby and volleyball, respectively), and individual contact and non-contact sports (karate and tennis, respectively) between the ages of 20 and 33 years (M = 24.37, SD = 2.85). The participants completed the Vividness of Visual Imagery Questionnaire, the Vividness of Movement Imagery Questionnaire-2, and the Mental Image Transformation Tasks. Results: A 2 ×2 × 2 (gender × 2 contact-no-contact × 2 sport type) between groups MANOVA showed differences in imagery ability by sport type. Practical indications deriving from the findings of this study can help coaches and athletes to develop mental preparation programs using sport-specific imagery.